Mitogenomic data to study the taxonomy of Antarctic springtail species (Hexapoda: Collembola) and their adaptation to extreme environments - Carapelli, Antonio; Fanciulli, Pietro Paolo; Frati, Francesco; Leo, Chiara (Polar Biology, 2019)
Mitochondrial DNA (mtDNA) encodes for proteins mainly involved in the oxidative phosphorylation process, and due to its molecular features, it is one of the most used molecular markers for phylogenetic and taxonomic purposes. Since mitochondria are the primary source of energy for aerobic organisms, it has been suggested that modifications of the mitochondrial genome’s features could be linked with major adaptive processes to particular environmental conditions. In this respect, Antarctic Collembola (springtails) may be considered an interesting model to study whether positive selective pressure has occurred, inducing significant changes in the mtDNA characteristics that have eventually led to cold adaptation. In this study, we describe the molecular features of the mitochondrial genome of Cryptopygus terranovus, a springtail species endemic to Victoria Land. Molecular data are also employed to support the new taxonomic placement of C. terranovus, and to establish if the conspecific lineages of Friesea antarctica, that lives in separated biogeographical regions of the Antarctic Continent, are indeed distinct species. Finally, all the mitochondrial genomes of springtails, so far sequenced, were applied for calculating the ratio (ω) of nonsynonymous versus synonymous nucleotide substitutions. This approach allowed us to investigate if Antarctic collembolans could have experienced Darwinian selective pressures compared to the non-Antarctic springtail species. Indeed, our data does indicate positive selection (ω > 1), suggesting that survival at extreme environmental conditions could be also related to mtDNA modifications.